Case report: Multiorgan involvement with congenital Zika syndrome - Cachay, Rodrigo; Schwalb, Alvaro; Watanabe, Takashi; Guzman, Doris; Jänisch, Thomas; Guillén-Pinto, Daniel; Gotuzzo, Eduardo (The American journal of tropical medicine and hygiene, 2020)
We report the case of an infant born with congenital Zika syndrome (CZS). During the largest Zika virus(ZIKV) outbreak in Peru, the mother presented with fever and rash that were confirmed to be due to ZIKV by real-time PCR.The infant was born with severe microcephaly. Imaging revealed corpus callosum dysgenesis, lissencephaly, ven-triculomegaly, and calcifications. Mild hypertrophic cardiomyopathy with diastolic dysfunction was reported in the echocardiogram. Valgus deviation of the lower extremities and a left clubfoot were diagnosed at birth. The hip ultrasoundshowed incipient signs of Graf type II dysplasia. The findings confirm that CZS is a multiorgan phenotype in whichmicrocephaly is merely the tip of the iceberg. A multidisciplinary approach is needed for the evaluation of these children.
Gesehen am 06.05.2021